STATE IMMUNITY FOR ECONOMIC ACTIVITIES: EXAMPLE OF AN ODIOUS PUBLIC DEBT - Dimitrijević, Marko B. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
Abstract: The subject of the analysis in this paper is to determine the essential features of an odious public debt (loan) in contemporary monetary law. In this context, the first part of the paper focuses on the concept and basic functions of the public debt in the theory and practice of monetary management and discusses the basic principles of public borrowing that ensure timely servicing of overdue monetary obligations and support fiscal responsibility and credibility of public loan subscribers. The second part of the paper deals with the concept of an odious public debt emission and its correlation with the state immunity for undertaking economic activities that are not in dispute in the field of fiscal and financial sovereignty but raises the question of the public monetary agent's responsibility (central banks and public debt management agencies) for the harm they may cause to others in their work. The subject of particular analysis in the paper is the need for the widespread use of the doctrine of odious public debt as a means creditors protection from subscribing to so-called bonds of dictatorial state regimes and the potential constitution of an international judicial forum that would have the responsibility to prevent the effects of odious public debt on time by early detection of bad intent by the debtor or extend the necessary period to examine such intentions before the conclusion of the contract, which, in the author's view, is a condition for credible public debt management policies.Keywords: monetary law, monetary management, odious public debt, monetary sovereignty, lex monetae.
Keywords: монетарно право; монетарно управљање; несавесни јавни дуг; монетарни суверенитет; lex monetae